Ex vivo myo-mechanical assessment of isolated rectus abdominis muscle in pregnancy-specific urinary incontinence: a cross-sectional study nested within the Diamater cohort - Carolina N. F. Carvalho; David R. A. Reyes; Juliana F. Floriano; Sofia B. C. V. Quiroz; Rafael G. Oliveira; Fernanda C. B. Alves; Gabriela A. Garcia; Luana F. Iamundo; Adriely B. M. Magyori; Caroline B. Prudencio; Patricia S. Rossignoli; Cristiane R. Pedroni; et al. (BioMedical Engineering OnLine)
Abstract Background Rectus abdominis muscle (RAM) myopathy is the underlying mechanism of pregnancy-specific urinary incontinence (PSUI), which has been shown to be a predictor of long-term urinary incontinence (UI). However, there is limited knowledge about selective ex vivo myo-mechanical assessment (MMA) of the RAM in healthy pregnant women, particularly those with PSUI. Results Our analysis revealed no specific quantitative parameters from the window analysis or contractile response of the RAM in ex vivo MMA. A gradual and consistent decline was predominantly observed in the peak and strength parameters for both groups. The qualitative contractile response analysis of the RAM using peak and strength parameters revealed three distinct behaviors under electrical stimulation: a progressive decrease in strength, sudden muscular arrest, and asynchrony with erratic fluctuations. In-depth quantitative analysis of the RAM ex vivo did not yield substantial differences between the two groups. However, qualitative analysis proved valuable in distinguishing the groups, revealing a tendency toward the loss of the progressive peak declines observed in the control group. Conclusion This study highlights the complexity of RAM myopathy in the context of PSUI and its potential impact on UI outcomes. Method In this cross-sectional study nested within a cohort, we examined ex vivo myography assessments in 87 mothers, comprising 48 with PSUI and 39 without PSUI, all of whom exhibited normal glucose tolerance. General data were extracted from our database, whereas RAM samples were collected during C-section for qualitative and quantitative ex vivo myography analysis, with a focus on initial and final baseline measurements, peak responses, strength, and duration times.